Tingkat Pengetahuan, Sikap, dan Tindakan Pola Hidup Masyarakat Kelurahan Utan Panjang Terhadap Covid-19 - Jakarta Pusat - Rabima Rabima; Dian Cahyanti (Syntax Corporation Indonesia, 2021)
This study aims to determine the level of knowledge, attitudes, and actions of the lifestyle of the people of the Utan Panjang village against Covid-19 - Central Jakarta. The research method uses quantitative descriptive with independent variables knowing the level of knowledge, attitudes, and actions of people's lifestyles and the dependent variable of covid-19 - Central Jakarta. Samples were taken by Random Sampling technique. The size of the sample in this study can be known by using the Slovin formula, the number of samples is 340 respondents. Using a questionnaire in data collection, the data can be analyzed using IBM SPSS 24. The results of the univariate test obtained the largest percentage at the age of 18-30 years (30.9%, 105 respondents), female gender (51.5%, 175 respondents), and SMA/SMK education (55.6%, 189 respondents). With the number of respondents who fall into the category of poor knowledge level (84 respondents), sufficient (157 respondents), and good (99 respondents) from a total of 340 respondents. With the number of respondents who fall into the category of poor attitude (90 respondents), enough (12 respondents), and good (238 respondents) from a total of 340 respondents. Meanwhile, the number of respondents who fall into the category of poor lifestyle (31 respondents), sufficient (63 respondents), and good (246 respondents) from a total of 340 respondents. The results of the bivariate test using the Pearson correlation method found that there was a relationship between knowing the level of knowledge, attitudes, and actions of the life pattern of the kelurahan utan Panjang community towards covid-19 - Central Jakarta.